Analisis Pengetahuan Masyarakat Dalam Pengelolaan Hutan Di Blok Pemanfaatan Kawasan Taman Hutan Raya Nuraksa, Provinsi Nusa Tenggara Barat - Annisa Aprilia; Markum; Budhy Setiawan (Agroinovasi: Jurnal Ilmu dan Teknologi Pertanian, 2024)
Forest conservation depends on community knowledge and practices about the benefits and advantages that can be obtained from the forest. These two points are fundamental characteristics to produce superior performance. In managing forests, knowledge and practice management are needed. To find out which knowledge is important and which knowledge needs improvement and to find out which practices are important and which practices need improvement can be done by gap analysis. The purpose of this study was to determine community knowledge in forest management in the utilization block of the Tahura Nuraksa area. The method used in this study is a combination method (mix method). The combination method combines qualitative and quantitative research to be used together. With the nature of descriptive research, descriptive is used to determine gaps in describing or providing an overview of community knowledge and practices in forest management. The data analysis used is a Likert scale with an average score. The results of the descriptive analysis of the Likert scale of the Selendang Rinjani Forest Farmer Group community have a level of knowledge that falls into the low category with a value of 26. The practice of the Selendang Rinjani Forest Farmer Group is in the medium category with a value of 32.